Humanist Expressive Utterance Function and Form in Teaching Learning Interaction at Vocational High School - Rini, Susilo; Wagiran, Wagiran (Pascasarjana Universitas Negeri Semarang, 2018)
Communication in teaching learning process needs utterance which is expressive and humanist, so that the message conveyed can be received by locutors. Humanist expressive speech act is needed both by teacher and students in class. This research is aimed to describe shape and function of humanism expressive utterance on teaching-learning process in industrial Tecknology vocational High School. The utterance action is classified into declarative, representative, expressive, directive and comissive. The discussion is focused on industrial Technologi vocational   high school.Utterans action on learning-teaching interaction in industrial Technology vocational high school. Collecting data uses sap tapped method. Research metod uses qualitive-descritive research. Speaking method is used to analyze shape and function of humanist expresive utterance. The research results are, first, humanist expresive utterance shape, includes, (a) direct utterance, is utterans which is appropriate beween modus and its function. Direct utterence modused imperative, declarative, interogatif, (b) indirect utterance is utteran which is not appropriate between modus and its function. Indirect utterance action modused interogative-imperative and declarative-imperative. Function of humanist expressve utterence (a) asking for forgive, (b) saying greting, (c) conveying grivance, (d) criticizing(e) complimenting, (f) allusing.